Improving spatial reuse and throughput via OBSS/PD in IEEE 802.11ax - Karakoç, Ali. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
The aim of this thesis is to improve spatial reuse by using special mechanisms in IEEE 802.11ax wireless local area networks. If there are numbers of basic service sets (BSSs) in the same vicinity, overlapping BSSs may create interference. In this situation, BSSs cannot transmit simultaneously, because of the collisions. Moreover, there may be spectral e ciency problems like \Hidden Node Problem" or \Exposed Node Problem", that may cause signi cant performance degradation to the system. In IEEE 802.11ax amendment, to address these spectral e ciency problems, a couple of mechanisms are introduced. One of the spectral e ciency mechanisms that address these problems is the overlapping BSS preamble detection (OBSS/PD) mechanism. OBSS/PD is a color-based mechanism that is used to detect and prevent overlapping BSS interference e ciently. In this thesis, we propose a rate-adaptive dynamic OBSS/PD threshold algorithm that dynamically adjusts the OBSS/PD threshold with respect to the changes in the channel conditions and selected data rates. Additionally, hidden and exposed node problems due to overlapping BSS are reduced. The proposed mechanism is designed to work along with the rate selection algorithms. In this study, the scenarios are performed with Minstrel and Thompson rate selection algorithms. The performance of the proposed mechanism has been compared with the legacy carrier sensitivity threshold algorithms (DSC and RTOT). Our algorithm has shown more stable performance than the reference algorithms in the Minstrel scenario, and none of the threshold algorithms have shown a signi cant performance enhancement relative to the others. When the Thompson rate selection algorithm is used, our proposed algorithm has shown a better performance and stability than the legacy carrier sensitivity threshold algorithms.
Keywords: IEEE 802.11 (Standard).; Wireless LANs.